EXPLORING COMMON STUDENT ERROR IN WRITING RECOUNT TEXTS: A CONTENT ANALYSIS STUDY - Setyaningrum, Riya Risqi; Faridah, Fita; Widyaiswara, Tiara (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
The study explores common errors in the generic structure components of recount text in VII-B students at MTs Putra-Putri Lamongan using of 20 students a content analysis approach. The finding indicates the most frequent error is the lack of orientation information, which occurs in approximately 60% of texts, where the students fail to introduce who, when, or where appropriately. In approximately 15% of texts, there is partial orientation. Regarding event sequences, mistakes are standard; 50% of texts have events in the wrong order, and 45% do not use time connectives, which cause the sequence to be unclear. In the re-orientation component, 70% of students leave out the closing reflective comment, tending to finish their recount suddenly, and 10% include poor or general closings. These findings identify priority areas of instructional focus to improve student competency in recount text writing through the significance of well-defined contextual introductions, sequential logic, and reflective conclusions.